Building health system capacity through medical education: a targeted needs assessment to guide development of a structured internal medicine curriculum for medical interns in Botswana - Peluso, MJ; Tapela, N; Langeveldt, J; Williams, ME; Mochankana, K; Motseosi, K; Ricci, B; Rodman, A; Haverkamp, C; Haverkamp, M; Maoto, R; Luckett, R; et al. (Ubiquity Press, 2018)
Background: Medical internship is the final year of training before independent practice for most doctors in Botswana. Internship training in Botswana faces challenges including variability in participants’ level of knowledge and skill related to their completion of medical school in a variety of settings (both foreign and domestic), lack of planned curricular content, and limited time for structured educational activities. Data on trainees’ opinions regarding the content and delivery of graduate medical education in settings like Botswana are limited, which makes it difficult to revise programs in a learner-centered way. Objective: To understand the perceptions and experiences of a group of medical interns in Botswana, in order to inform a large curriculum initiative. Methods: We conducted a targeted needs assessment using structured interviews at one district hospital. The interview script included demographic, quantitative, and free- response questions. Fourteen interns were asked their opinions about the content and format of structured educational activities, and provided feedback on the preferred characteristics of a new curriculum. Descriptive statistics were calculated. Findings: In the current curriculum, training workshops were the highest-scored teaching format, although most interns preferred lectures overall. Specialists were rated as the most useful teachers, and other interns and medical officers were rated as average. Interns felt they had adequate exposure to content such as HIV and tuberculosis, but inadequate exposure to areas including medical emergencies, non-communicable diseases, pain management, procedural skills, X-ray and EKG interpretation, disclosing medical information, and identifying career goals. For the new curriculum, interns preferred a structured case discussion format, and a focus on clinical reasoning and procedural skills. Conclusions: This needs assessment identified several foci for development, including a shift toward interactive sessions focused on skill development, the need to empower interns and medical officers to improve teaching skills, and the value of shifting curricular content to mirror the epidemiologic transition occurring in Botswana. Interns’ input is being used to initiate a large curriculum intervention that will be piloted and scaled nationally over the next several years. Our results underscore the value of seeking the opinion of trainees, both to aid educators in building programs that serve them and in empowering them to direct their education toward their needs and goals.